Upregulation of T-Cell-Specific Transcription Factor Expression in Pediatric T-Cell Acute Lymphoblastic Leukemia (T-ALL) - Müge Sayitoğlu; Yücel Erbilgin; Özden Hatırnaz; İnci Yıldız; Tiraje Celkan; Sema Anak; Ömer Devecioğlu; Gönül Aydoğan; Serap Karaman; Nazan Sarper; Çetin Timur; Ümit Üre; et al. (Turkish Journal of Hematology, 2012)
OBJECTIVE: T-cell acute lymphoblastic leukemia (T-ALL) is associated with recurrent chromosomal aberrations and abnormal ectopic gene expression during T-cell development. In order to gain insight into the pathogenesis of T-ALL this study aimed to measure the level of expression of 7 T-cell oncogenes (LMO2, LYL1, TAL1, TLX1, TLX3, BMI1, and CALM-AF10) in pediatric T-ALL patients. METHODS: LMO2, LYL1, TLX1, TLX3, BMI1, TAL1, and CALM-AF10 expression was measured using quantitative real-time PCR in 43 pediatric T-ALL patients. RESULTS: A high level of expression of LMO2, LYL1, TAL1, and BMI1 genes was observed in a large group of T-ALL. Several gene expression signatures indicative of leukemic arrest at specific stages of normal thymocyte development (LYL1 and LMO2) were highly expressed during the cortical and mature stages of T-cell development. Furthermore, upregulated TAL1 and BMI1 expression was observed in all phenotypic subgroups. In all, 6 of the patients had TLX1 and TLX3 proto-oncogene expression, which does not occur in normal cells, and none of the patients had CALM-AF10 fusion gene transcription. Expression of LYL1 alone and LMO2-LYL1 co-expression were associated with mediastinal involvement; however, high-level oncogene expression was not predictive of outcome in the present pediatric T-ALL patient group, but there was a trend towards a poor prognostic impact of TAL1 and/or LMO2 and/or LYL1 protooncogene expression. CONCLUSION: Poor prognostic impact of TAL1 and/or LMO2 and/or LYL1 proto-oncogene expression indicate the need for extensive study on oncogenic rearrangement and immunophenotypic markers in T-ALL, and their relationship to treatment outcome.